Peripheral urbanization and the UNCTAD III building in Santiago, Chile: continuity and disruption in grassroots engagement - Schlack, Elke; Varas, Paulina (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
Research has found that contestation has gained more attention in the urban development of Santiago de Chile. This contestation is seen by some scholars as the reaction to the predominant technocratic way in which consensus has been reached in the spatial planning of Santiago in the last decades. This article wants to showthe potentials for rekindling collaborative city-building experiences in a setting of governance and political democratic processes. Therefore, this study reviews specific experiences of production of urban space from the 1960’s 70’s in Santiago, noted for complex interactions and presence of organized resident, workers and grassroots actors. An emblematic public building – icon of the socialist regime – and peripheral housing estates – that represent the model of ‘self-organization’ – are shown to reveal the diversity of actors that were involved, the context of their formation and the interdependence they perform to reach consensus in urban development.